Pengaruh Modal Usaha Dan Karakteristik Wirausaha Terhadap Perkembangan UMKM Di Desa Sianting Anting Kecamatan Pangururan - Nainggolan, Alexandre Wilhem; Siagian, Nalom; Sinaga, Kepler (KALBISOCIO Jurnal Bisnis dan Komunikasi, 2025)
This study aims to determine how much influence Business Capital and Entrepreneurial Characteristics have, both partially and simultaneously, on the Development of MSMEs in Sianting Anting Village, Pangururan District, Samosir Regency. The type of research conducted is descriptive with a quantitative approach. The population in this study were MSME actors in Sianting Anting Village totaling 154 MSMEs and the sample used was a saturated sample. The results of the t-test show that the t-count value for the Business Capital variable has a value of 8.640, meaning> t-table, namely 1.97580 and a significance value of 0.000 <significant level of 0.05. So it can be concluded that Business Capital (X1) has a positive and significant influence on the MSME Development variable (Y). The t-count value for the Entrepreneurial Characteristics variable has a value of 7.029, meaning> t-table, namely 1.97580 and a significance value of the variable 0.000 <significant level of 0.05. So it can be concluded that Entrepreneurial Characteristics (X2) have a positive and significant influence on the MSME Development variable (Y).